Firms and social policy preferences under weak institutions: Evidence from Russia - Israel Marques II (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
When does business support the expansion of social policy in the developing world? Existing work on managers' preferences has tended to concentrate on the developed world, where governments can credibly commit to policy, tax evasion is constrained, and mechanisms exist to hold the bureaucracy accountable for policy implementation. In this paper, I relax these assumptions, arguing that weak institutions create opportunities for some firms to shift costs onto others: making social policy more attractive. I argue that firms with political connections are uniquely positioned to benefit from subsidies and property rights protection, which decreases the cost of social policy, while firms with low visibility can evade taxes and free-ride off universalistic social policy. Such firms will support social policy even where institutions are poor. I test this argument using a survey of 666 firms in 10 Russian regions.
URN:NBN:fi:bof-201802261242
Keywords: L21; L33; O15; O17; H53; 330